2015
DOI: 10.1007/s10867-015-9403-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the loading rate on compressive properties of goose eggs

Abstract: The resistance of goose (Anser anser f. domestica) eggs to damage was determined by measuring the average rupture force, specific deformation and rupture energy during their compression at different compression speeds (0.0167, 0.167, 0.334, 1.67, 6.68 and 13.36 mm/s). Eggs have been loaded between their poles (along X axis) and in the equator plane (Z axis). The greatest amount of force required to break the eggs was required when eggs were loaded along the X axis and the least compression force was required a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…This situation is different from the compression between two plane plates (see Fig. 1) where the compression rate is constant [13]. The egg shortening increases to some maximum and then slowly decreases.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…This situation is different from the compression between two plane plates (see Fig. 1) where the compression rate is constant [13]. The egg shortening increases to some maximum and then slowly decreases.…”
mentioning
confidence: 75%
“…The first data were obtained in the papers [1,5] for hen eggs. The effect of loading rate on the eggshell rupture force has been also found for Japanese quail eggs [12] and for goose eggs [13]. This procedure enables studying of the influence of loading rate over a relatively narrow range of this quantity.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Overall, these studies suggest that the radius of curvature strongly influences the breaking force, adding a layer of complexity to earlier studies which conclude that shell thickness is the primary factor affecting the force at which eggs fail under mechanical loading. Interestingly, two recent studies using Hopkinson split pressure bar have shown that the rupture force is independent of the eggshell curvature during dynamic loading [30,31].…”
Section: Introductionmentioning
confidence: 99%